1985
DOI: 10.1002/1097-0142(19850315)55:6<1322::aid-cncr2820550627>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Colon carcinoma in children and adolescents. A review of 30 cases

Abstract: Carcinoma of the large bowel is rare in persons under the age of 30, and generally presents with advanced stages of disease. From 1964 to 1984, 30 patients presented with nonfamilial large bowel malignancies. Seventeen patients were male, and 13 female (age range, 8–25 years). In 15 patients the primary was in the right transverse colon. In 26 patients the lesion was above the peritoneal reflection. Classification by Dukes' staging demonstrated Stage B in 3 patients, Stage C in 7 patients, and Stage D in 20 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
2
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 19 publications
4
82
2
2
Order By: Relevance
“…A total of 9% patients were in the age group < 30 years in the present study and found to have higher stage (10.9%) and higher grade (20.8%) tumors with the presence of lymphatic invasion (15%) and metastasis (10%). Different studies have investigated the incidence rates and the underlying causes of the development of the disease in the younger patients (Recio and Bussey, 1965;Mills and Shannon Allen, 1979;Gardner et al, 1981;Elliot and Steven, 1984;Rao et al, 1985;Palmer et al, 1991;Cozart et al, 1993;McGaharen et al, 1995). CRC has been found to have a worse prognosis among the younger patients which may be due to the advanced stage of the tumor at the time of diagnosis of this disease.…”
Section: Discussioncmentioning
confidence: 99%
“…A total of 9% patients were in the age group < 30 years in the present study and found to have higher stage (10.9%) and higher grade (20.8%) tumors with the presence of lymphatic invasion (15%) and metastasis (10%). Different studies have investigated the incidence rates and the underlying causes of the development of the disease in the younger patients (Recio and Bussey, 1965;Mills and Shannon Allen, 1979;Gardner et al, 1981;Elliot and Steven, 1984;Rao et al, 1985;Palmer et al, 1991;Cozart et al, 1993;McGaharen et al, 1995). CRC has been found to have a worse prognosis among the younger patients which may be due to the advanced stage of the tumor at the time of diagnosis of this disease.…”
Section: Discussioncmentioning
confidence: 99%
“…In children (age<15 years) the incidence is lower than in adolescents and only 12-20% of colorectal cancer in people under 20 years are detected before 10 years of age [3,4]. It is extremely infrequent in Caucasians whereas young Africans seem more susceptible to developing carcinoma of the colon [1]. Predisposing factors-familial polyposis of colon and other polyposis syndromes, ulcerative colitis, familial multiple cancer syndromes-are noted in 10% of the bowel cancers arising during childhood, which is far higher than in adult patients [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Primary gastrointestinal system malignancies constitute approximately 2% of paediatric neoplasm and, of these, colorectal carcinoma is the second most common malignancy after primary liver tumours [1]. Therefore, colorectal cancer remains unsuspected in children and most patients (60-80%) have Dukes' stage C or D disease at presentation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Se describió en todas las franjas etarias infantiles incluso en el recién nacido, pero los de la segunda década de edad parecen los más afectados. Entre los 0-9 años, su frecuencia es 0.4-0.9% y el sexo- (9)(10)(11) ratio es 2.2:1 .…”
Section: Discussionunclassified